Bridging policy and practice in climate change education: evidence from Northeast Thailand - Meekaew, Nattapon; Saenkum, Denpong (Frontiers in Education, 2025)
Climate change presents significant challenges to vulnerable regions, yet educational systems often lack systematic approaches to climate change education (CCE), particularly in resource-constrained settings. While research has examined CCE implementation in developed countries, little is known about effective delivery in climate-vulnerable regions. This study investigates the implementation of CCE in Northeast Thailand, emphasizing the interaction among teacher training, institutional support, and resource accessibility in a developing context where climate impacts directly affect communities. The study employed a sequential explanatory mixed-methods approach, integrating quantitative survey data from 400 teachers with qualitative insights from semi-structured interviews and focus group discussions among 15 teachers and 5 school administrators. Data were analyzed using multiple regression analysis and thematic analysis to identify key predictors of CCE effectiveness and contextual implementation factors. Regression analysis revealed teacher training as the strongest predictor of effective CCE implementation, followed by institutional support and resource availability. The study showed significant differences between urban and rural areas, with 85% of rural schools reporting insufficient resources compared to 40% of urban institutions. Additionally, 60% of teachers reported actively incorporating climate-related topics into their teaching. These findings demonstrate that successful CCE implementation requires the alignment of targeted teacher professional development, supportive institutional frameworks, and equitable resource distribution. Based on these findings, the study recommends establishing regional CCE teacher training centers, implementing resource-sharing networks between urban and rural schools, and developing locally adaptive curricula. This research provides an evidence-based framework for strengthening climate education in developing contexts, offering practical insights for educational policymakers working in climate-vulnerable regions.